Optimal transport for model calibration - Guo, I; Loeper, G; Obloj, J; Wang, S (Risk.net, 2022)
An overview of continuous (semi-martingale) optimal transport for model calibration is given in this paper. Ivan Guo et al present the general framework and then discuss the calibration of local, and local-stochastic, volatility models to European options and the joint VIX/SPX calibration problem as well as calibration to some path-dependent options